Microbial community dynamics linked to enhanced substrate availability and biogas production of electrokinetically pre-treated waste activated sludge. (October 2016) - Westerholm, Maria; Crauwels, Sam; Houtmeyers, Sofie; Meerbergen, Ken; Van Geel, Maarten; Lievens, Bart; Appels, Lise
Highlights: Electrokinetic pre-treatment enhanced substrate solubility and biogas production. Increased substrate availability altered bacterial community composition. Abundance of selected OTUs correlated with substrate solubility and biogas yield. Methanogenic community composition remained stable during operation. Abstract: The restricted hydrolytic degradation rate of complex organic matter presents a considerable challenge in anaerobic digestion of waste activated sludge (WAS). Within this context, application of pre-treatment of digester substrate has potential for improved waste management and enhanced biogas production. Anaerobic degradation of untreated or electrokinetically pre-treated WAS was performed in two pilot-scale digesters for 132 days. WAS electrokinetically pre-treated with energy input 0.066 kJ/kg sludge was used in a first phase of operation and WAS pre-treated with energy input 0.091 kJ/kg sludge was used in a second phase (each phase lasted at least three hydraulic retention times). Substrate characteristics before and after pre-treatment and effects on biogas digester performance were comprehensively analysed. To gain insights into influences of altered substrate characteristics on microbial communities, the dynamics within the bacterial and archaeal communities in the two digesters were investigated using 16S rRNA gene sequencing (pyrosequencing) and quantitative PCR (qPCR). Specific primers targeting dominant operation taxonomic units (OTUs) and members of the candidate phylum Cloacimonetes were designed to further evaluate their abundance and dynamics in the digesters. Electrokinetic pre-treatment significantly improved chemical oxygen demand (COD) and carbohydrate solubility and increased biogas production by 10–11% compared with untreated sludge. Compositional similarity of the bacterial community during initial operation and diversification during later operation indicated gradual adaptation of the community to the higher solubility of organic material in the pre-treated substrate. Further analyses revealed positive correlations between gene abundance of dominant OTUs related to Clostridia and Cloacimonetes and increased substrate availability and biogas production. Among the methanogens, the genus Methanosaeta dominated in both digesters. Overall, the results showed that electrokinetic pre-treatment of WAS increases substrate solubility and biogas production. Changes in bacterial community composition and abundances of dominant bacterial OTUs were observed during anaerobic degradation of pre-treated WAS, whereas the relative abundance of methanogenic community members remained stable.